Language and interpretation in Playback Theatre in a multilingual society: Drama for Life Playback Theatre Company, Wits University, Johannesburg, South Africa - Zanjam, Ngefor Shella (My University, 2011)
In this study, I explore the language of Playback Theatre and its application in a multi-lingual society through the experience of the Playback performers. I consider the performances and experience of the Drama for Life Playback Theatre Company at Wits University, Johannesburg, as application for the study. Literature on performance and ritual theory gave a framework for analysis while writings on language and the experience of community are included to illuminate the analysis of Playback Theatre performance in a multi-lingual society. The research report, based on principles of Action Research, has been undertaken using an ethnographic approach that draws on participant observation, informal individual interviews, researcher reflexivity and focus group discussion. The Drama for Life Playback Theatre Company is described and analysed giving the history and information on their practice. This leads to an analysis and a transcription of Playback Theatre performance. From this stage, the research report identifies and analyses elements of verbal and non-verbal language implicit in a Playback Theatre performance. Exploring the implication of this interactive form of theatre in a multilingual society shows that Playback Theatre can be applied for any context and in any setting as the experience of the performance relies on the non-verbal enactment of the stories by the actors. In the concluding section, the report reflects on the complex nature of writing up a report from a participant observer view when one does not hold a full position as a member of the group or community. The report has shown that the ritual frame of Playback Theatre allows for the actors to be able to hold and enact any story from audience members. The Playback actor remains the centre of action in the experience of Playback Theatre performance. This research has looked at language from the point of the actor which therefore means that there needs to be further research on the experience of the audience members in terms of knowing how effective Playback Theatre can be when experienced in multi-lingual societies.